The association between the use of intravenous drugs and the use of other substances among the inmates of Besut Rehabilitation Center in Terengganu, Malaysia - Rahman, Rusdi Abd
Objectives: This study was carried out to determine the prevalence of intravenous drug as well as the association between the use of intravenous drugs and the use of other substances such as cigarette, alcohol, volatile solvent, marijuana and psychoactive pill, among the inmates in Besut Rehabilitation Center, Terengganu, Malaysia.